2006
DOI: 10.1146/annurev.soc.32.082905.093959
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Prospects in the Study of Physician-Patient Interaction: 30 Years of Research

Abstract: ■ Abstract Working within the functionalist perspective that he did so much to develop, Parsons (1951) conceptualized the physician-patient relationship according to a normative framework defined by the pattern variable scheme. As Parsons clearly recognized, this normative conceptualization was one that empirical reality at best only approximates. In the 1970s, two major studies established doctor-patient interaction as a viable research domain. In the present review, we consider approaches to the medical int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
179
0
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(190 citation statements)
references
References 95 publications
0
179
0
11
Order By: Relevance
“…In working towards a definition of patient-centred care, Stewart (2001) identified the inherent tension in aiming to make -the implicit explicit‖ with the caveat that patient-centered care -is a holistic concept in which components interact and unite in a unique way in each patient-doctor encounter‖ and situated qualitative research as enabling us to -comes closer to conveying the qualities of such care‖ (p.444-445). Indeed, the application of Conversation Analysis (CA) helps to uncover the discursive patterns involved in the unfolding activity that constitutes a medical encounter (Heritage and Maynard, 2006). In the field of medical interpreting, new work is responding to calls for studies that -analyze interpreting as a situated, locally organized activity embedded in a particular setting‖ (Bolden, 2000, p.415).…”
Section: Introductionmentioning
confidence: 99%
“…In working towards a definition of patient-centred care, Stewart (2001) identified the inherent tension in aiming to make -the implicit explicit‖ with the caveat that patient-centered care -is a holistic concept in which components interact and unite in a unique way in each patient-doctor encounter‖ and situated qualitative research as enabling us to -comes closer to conveying the qualities of such care‖ (p.444-445). Indeed, the application of Conversation Analysis (CA) helps to uncover the discursive patterns involved in the unfolding activity that constitutes a medical encounter (Heritage and Maynard, 2006). In the field of medical interpreting, new work is responding to calls for studies that -analyze interpreting as a situated, locally organized activity embedded in a particular setting‖ (Bolden, 2000, p.415).…”
Section: Introductionmentioning
confidence: 99%
“…CA has, for example, been applied to aspects of primary care interactions (Heritage and Stivers, 1999;Heath, 1995); health visiting (Heritage and Sefi, 1995); counselling (Perakyla, 1995); mental health (Maynard, 1991); specialist neurological consultations (Plug and Reuber, 2007) and complementary and alternative medicine consultations in a variety of therapeutic modalities (Chatwin, 2013(Chatwin, , 2009(Chatwin, , 2008Ruusuvuori, 2005;Ruusuvuori and Lindfors, 2008;Chatwin and Collins, 2002). Many studies have been concerned with providing a broad socio-linguistic analysis of the features of particular environments, but work has also focused on exploring specific aspects of interaction within these settings e such as the ways in which patients 'frame' their presenting complaints (Heritage and Maynard, 2006); the ways in which medical consultations proceed in distinct phases (Heritage and Maynard, 2006;Robinson, 2003;Byrne and Long, 1976); how health professionals offer diagnostic information to patients (Heath, 1995); the 'question-driven' nature of doctor/patient interaction (Frankel, 1995;Maynard, 1991: Frankel, 1984; and various other aspects of how presenting complaints are offered, and treatment offers are negotiated (Entwistle et al, 2004). To date, there have been few CA based studies which have explored the comparative aspects of routine clinical encounters undertaken by different types of health professional, such as the COPD review consultations we present here, although notable exceptions are: Collins et al, 2005, andSmith et al, 2010, who examined the features of nurse encounters as well as those of GP's.…”
Section: Conversation Analysismentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Nearly half of the massage therapists practiced alone (45.7%), while 15.9% practiced with a chiropractor, 14.6% practiced in a salon or spa, 12.6% practiced with other massage therapists, and 12% worked in other practice settings.…”
Section: Participant Characteristicsmentioning
confidence: 99%
“…Researchers have found that the interpersonal behaviors of medical providers are related to patient outcomes; (6)(7)(8) these same behaviors have also been hypothesized to influence the outcomes of those receiving complementary and alternative medicine. (9) People seek massage therapy for symptom reduction, (10) requiring massage therapists to be better equipped with interpersonal communication skills to facilitate understanding of the client's condition.…”
Section: Introductionmentioning
confidence: 99%